Memahami Perilaku Pelanggan Blackberry di Surabaya: Peran Kesesuaian Diri dan Kesesuaian Fungsional - Aulia Rahman; Gancar Candra Premananto (Universitas Negeri Surabaya, 2018)
Sales of the BlackBerry (BB) in the global market continues to decline, but not so with the Indonesian market. The Indonesian market is unique. In this country, the madness of the BlackBerry is not like in other countries. In Indonesia, the BlackBerry dominates the smartphone market. Blackberry successful creating a trend, the BlackBerry boom in Indonesia due to the highly loaded BlackBerry messaging functions. This, along with the character of the people of Indonesia who love messaging, chat, and SMS. Consumers often compare their brand image with a picture of himself in making a purchase. The process of matching between the image of the brand with the consumer's self-concept is called the self-congruity. While consumers are trying to maximize the benefit (utility) in the purchase of products based on objective criteria such as price or performance of the product attributes influenced the functional congruity models. The purpose of this study to understand customer behavior Blackberry influence self congruity and functional congruity towards attitudes and customer loyalty. This study uses a quantitative approach to test the hypothesis. Using 110 respondents consumer Blackberry, generation X and generation Y. Data analysis technique used Partial Least Square (PLS). The results of this study are self congruity significantly influence the functional congruity, attitudes and brand loyalty. Furthermore, self congruity direct influence on brand loyalty. While the functional congruity the variables significantly influence attitudes, and attitudes affect brand loyalty. whereas age did not moderate the users self congruity and functional congruity toward customer attitudes